Child and adolescent suicide attempts, suicidal behavior, and adverse childhood experiences in South Africa: a prospective study - Cluver, L.; Orkin, M.; Boyes, Mark; Sherr, L. (Elsevier, 2015)
Purpose: This is the first known prospective study of child suicidal behavior in sub-Saharan Africa. Aims were to determine whether (1) cumulative exposure to adverse childhood experiences (ACEs) predicts later suicidality and (2) heightened risks are mediated by mental health disorder and drug/alcohol misuse. Methods: Longitudinal repeated interviews were conducted 1 year apart (97% retention) with 3,515 adolescents aged 10–18 years in South Africa (56% female; <2.5% refusal). Random selection of census enumeration areas from urban/rural sites within two provinces and door-to-door sampling included all homes with a resident adolescent. Measures included past-month suicide attempts, planning, and ideation, mental health disorders, drug/alcohol use, and ACE, for example, parental death by AIDS or homicide, abuse, and exposure to community violence. Analyses included multivariate logistic regression and multiple mediation tests.Results: Past-month suicidality rates were 3.2% of adolescents attempting, 5.8% planning, and 7.2% reporting ideation. After controlling for baseline suicidality and sociodemographics, a strong, graded relationship was shown between cumulative ACE and all suicide behaviors 1 year later. Baseline mental health, but not drug/alcohol misuse, mediated relationships between ACE and subsequent suicidality. Suicide attempts rose from 1.9% among adolescents with no ACE to 6.3% among adolescents with >5 ACEs (cumulative odds ratio [OR], 2.46; confidence interval [CI], 1.00–6.05); for suicide planning, from 2.4% to 12.5% (cumulative OR, 4.40; CI, 2.08–9.29); and for suicide ideation, from 4.2% to 15.6% (cumulative OR, 2.99; CI, 1.68–5.53). Conclusions: Preventing and mitigating childhood adversities have the potential to reduce suicidality. Among adolescents already exposed to adversities, effective mental health services may buffer against future suicidality.